The Solutions to the Orphan Works Problem A Comparative Study between Europe and the United States - Nissinen, Juha (fi=Turun yliopisto|en=University of Turku|, 2017)
Orphan works are works that are protected by copyright but whose right holders are not known or cannot be located. Because obtaining copyright permissions from the right holders is impossible, orphan works often cannot be used in secondary works nor they can be digitised. During the last ten years, there have been presented or adopted a multitude of solutions to address the orphan works problem. In Europe, the current solutions include an exception to the copyright, extended collective licensing and mandatory collective management of rights. In the United States, a model that limits the remedies available to the right holders has been suggested. In some US cases, fair use has been applied to mass digitisation projects involving orphan works. The purpose of this study is to compare the European and US orphan works solutions in order to gain a better understanding of their capability and effectiveness to address the orphan works problem. Moreover, this comparison between the European and US solutions makes possible to identify problems in the European orphan works regime and recommend on how to improve European law on orphan works.